Identification and characterization of transforming growth factor β-activated kinase 1 from Litopenaeus vannamei involved in anti-bacterial host defense. (May 2016) - Wang, Sheng; Li, Haoyang; Lǚ, Kai; Qian, Zhe; Weng, Shaoping; He, Jianguo; Li, Chaozheng
Abstract: LvTAK1, a member of transforming growth factor β-activated kinase 1 (TAK1) families, has been identified from Litopenaeus vannamei in this study. The full length of LvTAK1 is 2670 bp, including a 2277 bp open reading frame (ORF) that encoded a putative protein of 758 amino acids with a calculated molecular weight of ∼83.4 kDa LvTAK1 expression was most abundant in muscles and was up-regulated in gills after LPS, Vibrio parahaemolyticus, Staphhylococcu saureus, Poly (I:C) and WSSV challenge. Both in vivo and in vitro experiments indicated that LvTAK1 could activate the expression of several antimicrobial peptide genes (AMPs). In addition, the dsRNA-mediated knockdown of LvTAK1 enhanced the susceptibility of shrimps to Vibrio parahaemolyticus, a kind of Gram-negative bacteria. These results suggested LvTAK1 played important roles in anti-bacterial infection. CoIP and subcellular localization assay demonstrated that LvTAK1 could interact with its binding protein LvTAB2, a key component of IMD pathway. Moreover, over-expression of LvTAK1 in Drosophila S2 cell could strongly induce the promoter activity of Diptericin (Dpt), a typical AMP which is used to read out of the activation of IMD pathway. These findings suggested that LvTAK1 could function as a component of IMD pathway. Interestingly, with the over-expression of LvTAK1 in S2 cell, the promoter activity of Metchnikowin (Mtk), a main target gene of Toll/Dif pathway, was up-regulated over 30 times, suggesting that LvTAK1 may also take part in signal transduction of the Toll pathway. In conclusion, we provided some evidences that the involvement of LvTAK1 in the regulation of both Toll and IMD pathways, as well as innate immune against bacterial infection in shrimp. Highlights: The first TAK1 homolog (LvTAK1) is cloned and identified from shrimp ( Litopenaeus vannamei ). LvTAK1 can interact with LvTAB2. LvTAK1 can induce the expression of both Toll and IMD pathways target AMPs such as Metchnikowin and Diptericin. LvTAK1 regulates the transcription of AMPs in vivo and plays a protective role in Vibrio parahaemolyticus infection.